1997
DOI: 10.2307/3802582
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Power Analysis in Wildlife Research

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
218
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(222 citation statements)
references
References 35 publications
1
218
0
3
Order By: Relevance
“…analysis provides useful information, but retrospective power analysis (that uses only the data from a single experiment) provides no additional information that is not already implicit in the p value (e.g., Gerard, Smith, & Weerakkody, 1998;Hoenig & Heisey, 2001;Nakagawa & Foster, 2004;O'Keefe, 2007;Steidl, Hayes, & Schauber, 1997;Sun, Pan, & Wang, 2011;Thomas, 1997). Retrospective power analysis can, however, at least make explicit the probability of achieving various goals in the given experiment, even if that information is not useful for additional inference from the given data.…”
Section: Power Analysis For Bayesian Estimationmentioning
confidence: 99%
“…analysis provides useful information, but retrospective power analysis (that uses only the data from a single experiment) provides no additional information that is not already implicit in the p value (e.g., Gerard, Smith, & Weerakkody, 1998;Hoenig & Heisey, 2001;Nakagawa & Foster, 2004;O'Keefe, 2007;Steidl, Hayes, & Schauber, 1997;Sun, Pan, & Wang, 2011;Thomas, 1997). Retrospective power analysis can, however, at least make explicit the probability of achieving various goals in the given experiment, even if that information is not useful for additional inference from the given data.…”
Section: Power Analysis For Bayesian Estimationmentioning
confidence: 99%
“…(Steidl et al 1997). Les résultats ne montrent donc pas d'augmentation observable et mesurable de la croissance des tiges des peuplements éclaircis suite à l'intervention.…”
Section: Sapin Baumierunclassified
“…14, 2003 ment conventional VHF telemetry projects, or pro¬ ceed with the maximum number of collars that can be maintained within a specified budget. Such con¬ straints lead to reduced statistical power of subse¬ quent data analyses (Steidl et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, there has been no effort to estimate collar sample size requirements for this type of program, central to determining effectiveness of mitigation efforts. Additionally, sta¬ tistical analyses could suffer from lack of power (Steidl et al, 1997). It is noteworthy that earlier studies have identified potential negative impacts of the jet activity on caribou (Harrington & Veitch, 1991;Harrington & Veitch, 1992).…”
Section: Introductionmentioning
confidence: 99%